KAJIAN PENCITRAAN KOTA (CITY BRANDING) YOGYAKARTA Kesesuaian Antara Konseptual dan Faktual Berdasarkan Media Internet - , Stevina Fortunata, Ir. Ikaputra, M.Eng.Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the competition of tourism sector between Indonesia and other countries in the world, every region in Indonesia included Yogyakarta requires a city branding as an advertising. In reality however the city branding of Yogyakarta was percepted differently by tourists. This research aims at: 1) identifying the concept of city branding of Yogyakarta at the time being